2016
DOI: 10.1371/journal.pone.0148227
|View full text |Cite
|
Sign up to set email alerts
|

Whisker Deprivation Drives Two Phases of Inhibitory Synapse Weakening in Layer 4 of Rat Somatosensory Cortex

Abstract: Inhibitory synapse development in sensory neocortex is experience-dependent, with sustained sensory deprivation yielding fewer and weaker inhibitory synapses. Whether this represents arrest of synapse maturation, or a more complex set of processes, is unclear. To test this, we measured the dynamics of inhibitory synapse development in layer 4 of rat somatosensory cortex (S1) during continuous whisker deprivation from postnatal day 7, and in age-matched controls. In deprived columns, spontaneous miniature inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…5G; 17.25 +/-2.44 vs. 17.13 +/-1.86 spines/10 microns). Taken together, our data confirm that whisker deprivation induced a homeostatic response in the contralateral hemisphere 48 hours after trimming, as previously reported (Gainey et al, 2016(Gainey et al, , 2018Knott et al, 2002;Li et al, 2014).…”
Section: Sensory Deprivation Induces a Homeostatic Response In The Basupporting
confidence: 92%
See 1 more Smart Citation
“…5G; 17.25 +/-2.44 vs. 17.13 +/-1.86 spines/10 microns). Taken together, our data confirm that whisker deprivation induced a homeostatic response in the contralateral hemisphere 48 hours after trimming, as previously reported (Gainey et al, 2016(Gainey et al, , 2018Knott et al, 2002;Li et al, 2014).…”
Section: Sensory Deprivation Induces a Homeostatic Response In The Basupporting
confidence: 92%
“…Sensory deprivation of the visual cortex, for example, reduces cortical inhibition, which increases spontaneous activity and lowers the threshold for LTP (Benevento et al, 1992;Bridi et al, 2018;Kirkwood et al, 1996;Kuhlman et al, 2013). Similarly, whisker trimming, an established model for sensory deprivation of somatosensory (barrel) cortex (Gainey et al, 2016(Gainey et al, , 2018Gray et al, 2006), has been shown to increase the ratio of excitation to inhibition (E/I): while both excitation and inhibition decrease after whisker trimming, inhibition decreases more (Gainey et al, 2018;Li et al, 2014). Given the evidence that sensory deprivation alters both excitation and inhibition, we asked whether whisker trimming induces an upscaling or downscaling-like homeostatic PIN response.…”
Section: Sensory Deprivation Induces a Homeostatic Response In The Bamentioning
confidence: 99%
“…We also measured the miniature inhibitory postsynaptic currents (mIPSC) to test whether the increase in inhibitory synaptic density (Sarma et al, 2011) could also reflects an increase in local number of sites of GABAergic synapses. Moreover, as development of inhibitory circuit in neocortex can be driven by sensory experience, and the sensory‐deprived animals often show a weaker inhibition and persistence of immature synaptic phenotypes (Jiao et al, 2006; Kreczko et al, 2009; Gainey et al, 2016), we also studied the GABAergic synaptic transmission after early postnatal olfactory deprivation. Therefore, considering that the inhibitory cortical circuits in the aPC can be formed via combination of intrinsic neuronal and environmental changes during the maturation process, we evaluated the sIPSC and mIPSC in aPC of both hemispheres of unilateral naris‐occluded rats.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that our protocol of partial sensory deprivation (whisker trimming) was applied to adult mice only (3–4 months old) and did not include follicle removal or cauterization. Moreover, considering the short duration of the deprivation (7 days), we do not believe that the results of this study are a consequence of cortical map plasticity, widely described in neurodevelopmental and plasticity studies using the barrel-cortex system model (Van der Loos and Woolsey, 1973 ; Woolsey and Wann, 1976 ; Levin and Dunn-Meynell, 1991 ; Dunn-Meynell et al, 1992 ; Siucinska and Kossut, 1994 ; Melzer and Smith, 1996 ; Kossut and Juliano, 1999 ; Fox, 2002 ; Allen et al, 2003 ; Rema et al, 2003 ; Schierloh et al, 2003 ; Shepherd et al, 2003 ; Dubroff et al, 2005 ; Fox and Wong, 2005 ; Shoykhet et al, 2005 ; Frostig, 2006 ; Lee et al, 2007 ; Schubert et al, 2007 ; Drew and Feldman, 2009 ; Wu et al, 2011 ; Gainey et al, 2016 ; Jacob et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%